O wn thinking and transdisciplinary integration in the social epistemic (Andamios, Revista de Investigación Social, 2016)
Education evolves in a student’s life (ontogeny) and in the life of the school system (phylogeny). These routes can consolidate the continuity or a change for the formation of own thinking as a teaching strategy. The experience I present happened during the 2015-1 and 2016-1 terms of the study in Social Studies and Local Management at Unit ENES,UNAM Morelia in regard to the teaching of the subject Epistemology Research. I have based educational practice in collaboration dynamics, seeking to root cognitive training of one’s own thinking in young apprentices of social studies. The constant discovery, recovery of thinking in the present tense and mutual recognition produced synthetic results shown here for reflective unveiling.
Keywords: Own thinking; Transdisciplinary integration; Social epistemic; Social construction of knowledge